2016
DOI: 10.18632/oncotarget.13642
|View full text |Cite
|
Sign up to set email alerts
|

New differentially expressed genes and differential DNA methylation underlying refractory epilepsy

Abstract: Epigenetics underlying refractory epilepsy is poorly understood, especially in patients without distinctive genetic alterations. DNA methylation may affect gene expression in epilepsy without affecting DNA sequences. Herein, we analyzed genome-wide DNA methylation and gene expression in brain tissues of 10 patients with refractory epilepsy using methylated DNA immunoprecipitation linked with sequencing and mRNA Sequencing. Diverse distribution of differentially methylated genes was found in X chromosome, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…Lastly, Egr genes have been also reported in previous studies on epilepsy in the GASH/Sal hamster (López-López et al, 2017), in polycarpic-induced rat models (Lösing et al, 2017), in patients with refractory epilepsy (Liu et al, 2016), in the IC of the DBA/2J mice after induced audiogenic seizures (Li and Hu, 2005) and in an animal model of temporal lobe Epilepsy (Grabenstatter et al, 2014). Similarly, the genes Npas4, Junb, Fos and Fosb have also been related to epileptiform processes in animal models and epileptogenic tissue samples (Elliott and Gall, 2000;Beaumont et al, 2012;Liu et al, 2016;Lösing et al, 2017). Overall, the GO analysis of this molecular network demonstrated that several GO terms identified in this study have been related to epilepsy in previous studies on refractory epilepsy of the mesial temporal lobe (Bando et al, 2011) and in rat models of febrile seizures (Wang et al, 2014).…”
Section: Molecular Network Of Differentially Expressed Genesmentioning
confidence: 59%
See 1 more Smart Citation
“…Lastly, Egr genes have been also reported in previous studies on epilepsy in the GASH/Sal hamster (López-López et al, 2017), in polycarpic-induced rat models (Lösing et al, 2017), in patients with refractory epilepsy (Liu et al, 2016), in the IC of the DBA/2J mice after induced audiogenic seizures (Li and Hu, 2005) and in an animal model of temporal lobe Epilepsy (Grabenstatter et al, 2014). Similarly, the genes Npas4, Junb, Fos and Fosb have also been related to epileptiform processes in animal models and epileptogenic tissue samples (Elliott and Gall, 2000;Beaumont et al, 2012;Liu et al, 2016;Lösing et al, 2017). Overall, the GO analysis of this molecular network demonstrated that several GO terms identified in this study have been related to epilepsy in previous studies on refractory epilepsy of the mesial temporal lobe (Bando et al, 2011) and in rat models of febrile seizures (Wang et al, 2014).…”
Section: Molecular Network Of Differentially Expressed Genesmentioning
confidence: 59%
“…Npas4 gene is directly involved in activity-dependent gene expression control and regulation of long-lasting brain functions, such as memory formation, adaptation, and synaptic plasticity (Lin et al, 2008;Ye et al, 2016). Lastly, Egr genes have been also reported in previous studies on epilepsy in the GASH/Sal hamster (López-López et al, 2017), in polycarpic-induced rat models (Lösing et al, 2017), in patients with refractory epilepsy (Liu et al, 2016), in the IC of the DBA/2J mice after induced audiogenic seizures (Li and Hu, 2005) and in an animal model of temporal lobe Epilepsy (Grabenstatter et al, 2014). Similarly, the genes Npas4, Junb, Fos and Fosb have also been related to epileptiform processes in animal models and epileptogenic tissue samples (Elliott and Gall, 2000;Beaumont et al, 2012;Liu et al, 2016;Lösing et al, 2017).…”
Section: Molecular Network Of Differentially Expressed Genesmentioning
confidence: 84%
“…Neurons contribute with slightly higher number of altered gene transcripts when comparing to a amygdala stimulation model of epilepsy while glia contributes with a higher number of differentially expressed genes when comparing to a traumatic brain injury model of epilepsy [29]. Within up- and downregulated gene transcripts from a study on refractory human TLE, neurons and glia exhibit an almost even number of gene transcripts [57]. For an overview of essential up- and downregulated pathways see Tables 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…Krasniqi et al recently clarified the mechanism of renin in brain induced neuropathology like epilepsy, and discovered renin inhibitors may have therapeutic applications for epilepsy treatment [ 30 ]. Liu et al reported that abnormal neuroactive ligand-receptor interactions enhance the susceptibility to epileptic seizures [ 31 ]. Moreover, Risley et al proposed that the cGMP-PKG signaling pathway was a hidden new target for studying epilepsy mechanisms [ 32 ].…”
Section: Discussionmentioning
confidence: 99%